Quality evaluation of metabolic and bariatric surgical guidelines - Qin, Zi-Han; Yang, Xin; Zheng, Ya-Qi; An, Li-Ya; Yang, Ting; Du, Yu-Lu; Wang, Xiao; Zhao, Shu-Han; Li, Hao-Han; Sun, Cheng-Kai; Sun, Da-Li; Lin, Yue-Ying (Frontiers in Endocrinology, 2023)
Objective: To evaluate the quality of surgical guidelines on bariatric/metabolic surgery. Methods: Four independent reviewers used the AGREE II tool to assess the methodological quality of the included guidelines and conducted a comparative analysis of the main recommendations for surgical methods of these guidelines. Results: Nine surgical guidelines were included in this study. Five articles with AGREE II scores over 60% are worthy of clinical recommendation. The field of rigor of development was relatively low, with an average score of 50.82%. Among 15 key recommendations and the corresponding best evidence in the guidelines, only 4 key recommendations were grade A recommendations. Conclusions: The quality of metabolic and bariatric guidelines is uneven, and there is much room for improvement.